Prolactin gene polymorphism in indigenous and crossbred cattle of north east India - LALHRUAITLUANGI, LALHRUAITLUANGI; GOHAIN, CHUKHAM; YORE, KEYOLENU; SINGH, N SHYAMSANA; MAYENGBAM, PRAVA; TOLENKHOMBA, T C (The Indian Journal of Animal Sciences, 2019)
Bovine PRL gene is considered one of the important hereditary components of milk productivity, thus seems to be an excellent candidate gene for milk production traits. The study was conducted to study the distribution pattern of allelic variants at the prolactin-RsaI locus in 210 indigenous cattle of north east India (viz. Manipur, Mizoram, Nagaland, Tripura, Asom and Meghalaya,) and crossbred cattle of Mizoram. PCR-RFLP genotyping of a 156 bp fragment of prolactin (PRL) in exon 3 revealed two different allelic variants. The predominant genotype (s) were AB (0.40) and BB (0.40) in indigenous cattle of Manipur, BB in Mizoram (0.57), AB in indigenous cattle of Nagaland (0.50) and Meghalaya (0.63). Whereas in Tripura and Asom indigenous cattle, AA was the most common genotype (0.40 and 0.60). However, AB (0.80) was markedly higher in crossbred (HF Ã— indigenous) cattle. All the six indigenous cattle populations conforming to equilibrium indicated lack of selection pressure for PRL gene in these cattle population. The most frequent allele was A allele in the indigenous cattle of Nagaland (0.55), Tripura (0.55) and Asom (0.70) and B allele in indigenous cattle of Manipur (0.60) and Mizoram (0.73). Whereas, in Meghalaya indigenous and crossbred cattle, both alleles were present in equal frequencies. The findings of differences in the distributions of allelic and genotype variants of PRL-RsaI locus among the indigenous cattle populations of six states of north east India, suggested the presence of scope for genetic selection for milk production traits.